THE EFFECT OF WORK STRESS AND WORK-LIFE BALANCE ON AFFECTIVE COMMITMENT PADA PG XYZ - Deo Satria Putera; Khoirur Rozaq (Universitas Negeri Surabaya, 2025)
This study aims to analyze the influence of Work Stress and Work-life Balance on Affective Commitment among employees of PG XYZ. The research employs a quantitative approach using a saturated sampling technique involving 105 respondents from various organizational divisions. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with the assistance of SmartPLS 3.0 software. The results indicate that Work Stress has a positive effect on Work-life Balance, while Work-life Balance has a positive and significant effect on Affective Commitment. These findings suggest that work stress, when experienced at a manageable level, does not always lead to negative outcomes. Instead, it can encourage employees to adapt, remain resilient, and maintain balance between work demands and personal life. Employees who experience a favorable level of work-life balance tend to develop stronger emotional attachment, loyalty, and a sense of belonging to the organization. Therefore, effective management of work stress and consistent organizational support for work-life balance are essential to strengthen affective commitment and ensure sustainable organizational performance.